Correlation of Adiponectin Gene Polymorphisms rs266729 and rs3774261 With Risk of Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Zheng, Yong-Tian; Xiao, Tian-Mei; Wu, Chan-Xian; Cheng, Jin-Yan; Li, Le-Yu (Frontiers in Endocrinology, 2022)
Background: Increasing evidence has suggested an association of adiponectin gene polymorphisms rs1501299, rs2241766, rs266729 and rs3774261 with risk of nonalcoholic fatty liver disease (NAFLD). This correlation has been extensively meta-analyzed for the first two polymorphisms, but not the second two. Methods: The PubMed, EMBASE, Google Scholar, and China National Knowledge Infrastructure databases were searched for relevant literature. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated. Results: A total of 10 case-control studies on rs266729 (2,619 cases and 1,962 controls) and 3 case-control studies on rs3774261 (562 cases and 793 controls) were included. Meta-analysis showed that rs266729 was associated with significantly higher NAFLD risk based on the following five models: allelic, OR 1.72, 95% CI 1.34-2.21, P < 0.001; recessive, OR 2.35, 95% CI 1.86-2.95, P < 0.001; dominant, OR 1.84, 95% CI 1.34-2.53, P < 0.001; homozygous, OR 2.69, 95% CI 1.84-3.92, P < 0.001; and heterozygous, OR 1.72, 95% CI 1.28-2.32, P < 0.001. This association between rs266729 and NAFLD risk remained significant for all five models among studies with Asian, Chinese and Caucasian samples. The rs2241766 polymorphism was associated with significantly higher NAFLD risk according to the recessive model (OR 1.87, 95% CI 1.15-3.04, P = 0.01). Conclusion: Polymorphisms rs266729 and rs3774261 in the adiponectin gene may be risk factors for NAFLD. These findings may pave the way for novel therapeutic strategies, but they should be verified in large, well-designed studies.